Recurrent gastrointestinal bleeding in a patient with Eisenmenger syndrome using bosentan - SARI, İBRAHİM; TİGEN, MUSTAFA KÜRŞAT (Bentham Science Publishers, 2013)
Eisenmenger syndrome is associated with irreversible increase in pulmonary vascular resistance causing reduced survival. Bosentan, a non-selective endothelin receptor antagonist is the commonly used specific pulmonary arterial hypertension drug in Eisenmenger syndrome. In this paper, we present a case of recurrent gastrointestinal bleeding in a 23-year-old female with Eisenmenger syndrome who was only under bosentan treatment, which has not been reported previously. Most common adverse effect of bosentan is elevation in the liver enzymes however, bleeding complication is very rare. On the contrary, it was proposed that bosentan might be a potential protector against hyperacidity and mucosal erosion that occur as a consequence of stress. Although the mechanistic relationship of bleeding tendency and role of Eisenmenger syndrome concomitant with bosentan treatment is far from conclusive statement for now, this association warrants and should draw attention of clinicians and researches in this field. © 2013 Bentham Science Publishers.
Keywords: Bosentan; Congenital heart disease; Eisenmenger; Gastrointestinal bleeding; Pulmonary hypertension